EMPOWERING WOMEN: CATALYSTS FOR NATIONAL COHESION IN KENYA - O’Brien, Liam; Aoife , Murphy (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
National cohesion and integration, as elucidated by Kumalo and Sigsworth (2016), embodies a multifaceted process and a consequential state in which all citizens are empowered to perceive and experience their membership in a collective community, united in a common pursuit, confronting shared challenges, and embracing shared opportunities. Facilitating this intricate dynamic is the National Cohesion and Integration Commission (NCIC), a governmental institution entrusted with the mission of forging a unified national community and fostering harmonious coexistence among the diverse Kenyan populations